Materials-based drug delivery approaches: Recent advances and future perspectives - Pei JinJin; Yan Yuqiang; Palanisamy Chella Perumal; Jayaraman Selvaraj; Natarajan Prabhu Manickam; Umapathy Vidhya Rekha; Gopathy Sridevi; Roy Jeane Rebecca; Sadagopan Janaki Coimbatore; Thalamati Dwarakesh; Mironescu Monica (Green Processing and Synthesis, 2024)
Materials-based drug delivery approaches have garnered substantial attention in recent years due to their potential to revolutionize pharmaceutical interventions. This abstract provides a concise overview of recent advancements and future prospects in this rapidly evolving field. Materials such as nanoparticles, liposomes, polymers, and hydrogels have emerged as versatile carriers for drug delivery. These materials facilitate precise control over drug release kinetics, enabling targeted and sustained therapeutic effects. Smart materials with responsiveness to external stimuli or physiological conditions have further enhanced drug delivery precision. Personalized medicine approaches are gaining traction, tailoring drug delivery systems to individual patient profiles and needs. The horizon for materials-based drug delivery is bright. Ongoing research is focused on refining material design, streamlining production processes, and ensuring safety profiles. Collaborative efforts among researchers, clinicians, and industry stakeholders are crucial for translating these advancements into clinical practice. Additionally, the convergence of drug delivery with diagnostics and imaging holds immense potential for personalized and efficient healthcare solutions. As materials-based drug delivery continues to evolve, it stands poised to reshape the landscape of pharmaceuticals, offering the promise of more effective and patient-centered therapies for a wide range of medical conditions.